STUDY OF THE ESCAPE BEHAVIOR OF BUTTERFLYFISH (CHAETODONTIDAE) ON BUTON POT FISHING GEAR - Kedswin G. Hehanussa; Julian Tuhumury; Christian Ernsz Pattipeiloh; Semuel F. Tuhumury; Haruna Haruna (INFOKUM, 2022)
The pot construction used by fishermen is currently contrary to the Sustainable Development Goals (SDGs) which focus on the sustainable development of marine resources. The purpose of this study was to analyze the behaviour of the butterflyfish when they entered and escaped from the button pot. The research was conducted in April-May 2020. The data collected was in the form of types and body circumferences of fish that passed to the cover net. The results showed that a total of 353 fish were caught. The total number of fish caught was only 2.83% of the fish that escaped into the cover net which was dominated by fish from the Chaetodontidae family. The pattern of behaviour of the butterfly fish starts from when the fish approaches the pot (nearfild), when it enters the trap (ingress), and when it escapes, it has the same behaviour pattern as reef fish in general, namely spinning, walking along walls, and or swim while looking for gaps that can escape.